Analysis and modification of traditional games and sports towards their correct use in educational contexts - Antonio Méndez-Giménez; Javier Fernández-Río (FEADEF, 2011)
This article supports the idea of modifying traditional games and sports in order to provide students with significant educational experiences. First, a structural-functional analysis of traditional games is presented. Second, a teaching strategy to enhance their potential in physical education classes is introduced. Third, an approach to make traditional games more vivid for students is offered. The structure of each of the traditional games' categories is revised, and a few changes are introduced bearing in mind the children's characteristics and the school context's limitations. Finally, homemade materials are presented as a perfect tool for these changes, and to foster children's participation and motivation on traditional games